2004
DOI: 10.2174/0929867043455756
|View full text |Cite
|
Sign up to set email alerts
|

Development of Vascular Endothelial Growth Factor Receptor (VEGFR) Kinase Inhibitors as Anti-Angiogenic Agents in Cancer Therapy

Abstract: Among the known angiogenic growth factors and cytokines implicated in the modulation of normal and pathological angiogenesis, the VEGF family (VEGF-A, VEGF-B, VEGF-C, VEGF-D) and their corresponding receptor tyrosine kinases [VEGFR-1 (Flt-1), VEGFR-2 (Flk-1, KDR), and VEGFR-3 (Flt-4)] play a paramount and indispensable role in regulating the multiple facets of the angiogenic and lymphangiogenic processes, as well as the induction of vascular permeability and inflammation. The receptor VEGFR-2/KDR is the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 0 publications
1
76
0
3
Order By: Relevance
“…A fundamental approach to inhibit angiogenesis during tumorigenesis is the disruption of VEGF/VEGFR-2 pathway. 41 This could suppress tumor growth by limiting their blood supply, by changing the morphology, wall structure and function of tumor vasculature to a more normal fashion, 42 and thus improving drug penetration in tumors, and also by blocking VEGF autocrine pathway and thus reducing uncontrolled neoplastic cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fundamental approach to inhibit angiogenesis during tumorigenesis is the disruption of VEGF/VEGFR-2 pathway. 41 This could suppress tumor growth by limiting their blood supply, by changing the morphology, wall structure and function of tumor vasculature to a more normal fashion, 42 and thus improving drug penetration in tumors, and also by blocking VEGF autocrine pathway and thus reducing uncontrolled neoplastic cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…41 The most studied is SU5416 (semaxanib), which also presents inhibitory activity towards VEGFR-1. Studies in mice with transgenic prostate adenocarcinoma (TRAMP model) 43 revealed a significant decrease in intratumor microvessel density, an increment in cancer cell's apoptotic index, and pronounced regions of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focused on the CSI-SSL scores of a hairpin polyamide (PA-4) that targets the binding sites of the hypoxia induced transcription factor, HIF-1α. PA-4 binding to HIF-responsive-elements (HREs) blocks the activation of the hypoxia induced genes (18), including VEGF, a cytokine that is implicated in cancer and angiogenesis (43). Blocking HIF-1α dependent expression of VEGF suffices for averting tumorigenesis, thus marking this binding event as a target for therapeutic intervention.…”
Section: Landscapes Define Binding Energetics Across the Entire Sequencementioning
confidence: 99%
“…Notably, two of the most potently inhibited kinases were KDR (VEGFR-2, IC 50 = 12 nM) and Flt-4 (VEGFR-3, IC 50 = 6 nM), two receptor tyrosine kinases that are implicated in survival and development of tumor vasculature and which have also attracted much attention as potential targets for therapeutic intervention. 19 Effects of EXEL-9844 on Cdc25A induction and Chk1 activation. Previous studies have shown that treatment of cells with gemcitabine induces Chk1 and Chk2 phosphorylation.…”
Section: Exel-9844 Is a Potent Atp-competitive Inhibitor Of Chk1mentioning
confidence: 99%